2018
DOI: 10.1097/md.0000000000010075
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of endothelin receptor antagonist bosentan for pulmonary arterial hypertension associated with congenital heart disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
11
1
5
Order By: Relevance
“…20 Many studies have shown that the usage of drugs has certain impact on congenital heart disease, such as anti-infective drugs, sulfonamides have significant impact on the normal development of cardiovascular system, but the relationship between penicillin and congenital heart disease is not certain. 21,22 Antiasthma, antidepressant, antifungal drugs and drugs for treating hypertension and hypothyroidism all increased the incidence of congenital heart disease. 23 Several large-scale studies have shown that pregnant women who took progesterone, amphetamine, anticancer drugs and methionine in the early pregnancy significantly increased the risk of developing CHD in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…20 Many studies have shown that the usage of drugs has certain impact on congenital heart disease, such as anti-infective drugs, sulfonamides have significant impact on the normal development of cardiovascular system, but the relationship between penicillin and congenital heart disease is not certain. 21,22 Antiasthma, antidepressant, antifungal drugs and drugs for treating hypertension and hypothyroidism all increased the incidence of congenital heart disease. 23 Several large-scale studies have shown that pregnant women who took progesterone, amphetamine, anticancer drugs and methionine in the early pregnancy significantly increased the risk of developing CHD in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, la [endotelina-1]p (vasoconstrictor endotelial) continúa elevada, llevando a HAP persistente. Ante esto, algunos pacientes se conservan estables por un periodo de 3-5 años; en otros, el deterioro es rápido, lo que conduce a la falla ventricular derecha y muerte 14 .…”
Section: Discussionunclassified
“…Recently, the MAESTRO study (macitentan in Eisenmenger syndrome to restore exercise capacity) did not show results that were superior to placebo in regards to the primary end-point of change from baseline at the end of 16 weeks of treatment. 6 Nevertheless, the metaanalysis with 456 pooled PAH-CHD patients treated by bosentan as an adds on therapy 7 showed significant improvement in the 6MWD and with respect to the World Health Organization functional class (FC) and an additional statistically significant difference in mean pulmonary arterial pressure (mPAP) and pulmonary vascular resistance index (PVRi). These mixed outcomes led to a hesitation in adding combination therapy, as recommended by the 2015 European Society of Cardiology (ESC)/European Respiratory Society (ERS) pulmonary hypertension (PH) guidelines for a risk assessment strategy.…”
Section: Introductionmentioning
confidence: 99%